The impact of poor reading skills on Grade 12 isiXhosa Home Language exam results - Cutalele-Maqhude, Pumla (South African Journal of African Languages, 2023)
IsiXhosa is one of the 11 official languages offered as a subject in the South African school curriculum at Home Language (HL) level. The examination of this subject in grade 12 (the school-exit year) consists of three papers: Paper 1 (P1), which focuses on reading for understanding and language usage; Paper 2 (P2), which focuses on reading for analysis using prescribed genres; and Paper 3 (P3), which focuses on writing. The Department of Basic Education (DBE) publishes a diagnostic report after every examination session, following the completion of marking of the final examinations, detailing the performance of the grade 12 learners in each subject written. The 2018 and 2019 reports show that the performance of candidates in isiXhosa HL is poor and suggests that they cannot read for understanding. This study sought to analyse the impact of poor literacy skills on grade 12 candidates' performance in the isiXhosa HL final examinations. This was done by analysing the DBE's 2018 and 2019 isiXhosa HL Diagnostic Reports for P1 and determining how a lack of reading skills affects learners' comprehension and analysis skills. The South African Curriculum and Assessment Policy Statements (CAPS) emphasise the importance of reading for different purposes. The findings of this study suggest that learners do not have a solid foundation in reading and textual analysis and that reading is not given priority in the classroom, which ultimately leads to poor performance. The article concludes that reading and academic performance go hand in hand and that learners should be exposed to different texts; this can be achieved when teachers prepare well for their reading lessons and use not only the prescribed works. Furthermore, every learner should be given a chance to read, as no learner will ever perform well in their academics if their reading skills are poor.